A Rare Case of Single Coronary Artery: Getting to the Heart of the Matter - (:unkn) unknown (UBIQUITY PRESS LTDUnit 3N, 6 Osborn Street, LONDON E1 6TD, ENGLAND, 2023)
Single coronary artery anomaly represents a particularly rare entity, which may present with variable clinical scenarios, but in most cases remains asymptomatic. It is considered to be one of the pathological states to cause sudden death, especially in young adults [1]. We hereby report a rare case of a R-III type of single coronary artery as classified by Lipton et al., which is only about 15% of all the cases of coronary anomalies. Coronary CT angiography as well as invasive coronarography provide accurate details regarding the origin, course and termination of coronary anomalies, as well as evaluation of associated coronary lesions, further guiding the optimal treatment strategy in each case. Teaching Point: The main teaching point of this case report is to clearly underline the importance of coronary CT angiography in obtaining a comprehensive evaluation of coronary artery anatomy and associated coronary lesions, representing important aspects, which further guide accurate treatment and management.